2020
DOI: 10.1002/cey2.35
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐organic framework‐derived Fe/Cu‐substituted Co nanoparticles embedded in CNTs‐grafted carbon polyhedron for Zn‐air batteries

Abstract: Metal‐organic frameworks (MOFs) and MOF‐derived materials have attracted great attention as alternatives to noble‐metal based electrocatalysts owing to their intriguing structure properties, especially for high efficiency and stable oxygen reduction reaction (ORR). Herein, we employed a one‐pot reaction to make a multimetal (Fe, Co, Cu, and Zn) mixed zeolitic imidazolate framework (MM‐ZIF) via adopting a simple in situ redox reaction. Further pyrolysis of the target MM‐ZIF, a highly porous carbon polyhedron (F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(69 citation statements)
references
References 46 publications
4
61
0
Order By: Relevance
“…36,37 Specially, the content of pyridinic-N and F I G U R E 2 A, X-ray diffraction pattern of the CC-A-N@Co-NCNT and CC-A-N. B, Raman scattering spectra of CC-A-N@Co-NCNT, CC-A-N@Co, and CC-A-N, high-resolution elemental X-ray photoelectron spectras of Co-NCNT: (C) C 1s, (D) N 1s (E) Co 2p, and (F) O 1s graphitized-N accounts for approximately 97% of the total nitrogen in the structure, which are believed to be the active sites for ORR, thus favorable ORR activity is expected. 38 The high-resolution Co 2p 3/2 spectrum of Co-NCNT is shown in Figure 2E. Three peaks at 779.8, 781.8, and 785.7 eV can be identified as Co 3+ , Co 2+ , and satellite peak of Co 2+ , respectively.…”
Section: Resultsmentioning
confidence: 97%
“…36,37 Specially, the content of pyridinic-N and F I G U R E 2 A, X-ray diffraction pattern of the CC-A-N@Co-NCNT and CC-A-N. B, Raman scattering spectra of CC-A-N@Co-NCNT, CC-A-N@Co, and CC-A-N, high-resolution elemental X-ray photoelectron spectras of Co-NCNT: (C) C 1s, (D) N 1s (E) Co 2p, and (F) O 1s graphitized-N accounts for approximately 97% of the total nitrogen in the structure, which are believed to be the active sites for ORR, thus favorable ORR activity is expected. 38 The high-resolution Co 2p 3/2 spectrum of Co-NCNT is shown in Figure 2E. Three peaks at 779.8, 781.8, and 785.7 eV can be identified as Co 3+ , Co 2+ , and satellite peak of Co 2+ , respectively.…”
Section: Resultsmentioning
confidence: 97%
“…They found that the metal ratios in these ternary alloys can be easily manipulated through regulating the dosage of precursors, which could affect the number of charger distribution between alloys and carbon shells at the same time. Guo and co-workers [137] utilized the simple redox reaction between Figure 9. a) Formation of FeCo alloy on carbon cage.…”
Section: Multimetal Nps and Carbon Compositesmentioning
confidence: 99%
“…Metal–organic frameworks (MOFs) with 3D ordered porous structure have been widely utilized to prepare ADMCs materials. [ 90,91 ] Atomically dispersed metal ions can be easily introduced in the metal nodes, organic ligands, or pores of MOFs because of their unique characteristics, including organic–inorganic hybrid nature, large surface area, well‐defined porosity, tunable chemical composition, and adjustable functionality. [ 92 ] Moreover, the uniformly distributed metal ions in pristine MOFs can be converted into ADMCs through simple heat treatment, forming the atomically dispersed metal sites anchored in MOF‐derived carbon materials.…”
Section: Defect Chemistry Of Bifunctional Electrocatalystmentioning
confidence: 99%